Self-Contamination and Failure Modes During PPE Doffing: A Comparison of Two Powered Air-Purifying Respirator Hoods. (October 2020) - Erukunuakpor, Kimberly; Kraft, Colleen; Casanova, Lisa
Abstract : Background: High-level personal protective equipment (PPE) protects healthcare workers (HCWs) during the care of patients with serious communicable diseases. Doffing body fluid–contaminated PPE presents a risk of self-contamination. A study assessing HCW failure modes and self-contamination with viruses during PPE doffing found that, of all PPE items, the highest number of doffing failure modes and highest self-contamination risk occurred during removal of the 1-layer powered air-purifying respirator (PAPR) hood. Hood type may affect contamination risk; however, no experimental evidence exists comparing hood types. Objective: We quantified and compared the risk of self-contamination with viruses during doffing of a 1e-layer versus a 2-layer PAPR hood. Methods: In this study, 8 HCWs with experience using high-level PPE donned PPE contaminated on 4 prespecified areas with 2 surrogate human viruses, bacteriophage MS2 (a nonenvelope virus) and Φ6 (an enveloped virus). They completed a clinical task then doffed PPE according to a standard protocol. Following doffing, inner gloves, hands, face, and scrubs were sampled for viral contamination using infectivity assays. HCWs performed the entire sequence twice, first with a 1-layer hood with 1 shroud then with a 2-layer hood with 2 shrouds. The Wilcoxon rank-sum test was used to compare viral contamination between the 2 hood types. HCWs were video-recorded to identify failure modes in their doffing process using a failure modes and effects analysis to identify ways that individual actions deviated from optimal behavior. Results: Φ6 transfer to hands, inner gloves, and scrubs were observed for 1 HCW using the 1-layer hood versus scrubs only for 1 HCW using the 2-layer hood. MS2 transfer to hands was observed for 2 HCWs using the 1-layer hood versus none using the 2-layer hood. Inner glove contamination was observed for 6 of 8 HCWs using the 1-layer hood versus 2 of 8 using the 2-layer hood. Conclusions: A significantly higher number of MS2 virus was recovered on the inner gloves of HCWs using the 1-layer versus the 2-layer hood (median difference, 2.27×10 4 ; P = .03). In addition, 31 failure modes were identified during removal of the 2-layer hood versus 13 failure modes for the 1-layer hood. The magnitude of self-contamination depends on the type of PAPR hood used. The 2-layer hood resulted in significantly less inner glove contamination than the 1-layer hood. However, more failure modes were identified during the doffing process for the 2-layer hood. In conclusion, the failure modes identified during the use of the 2-layer hood were less likely to result in self-contamination compared to the failure modes identified during use of the 1-layer hood. Funding: None Disclosures: None